Assessing the Effectiveness of Peer Tutoring in Improving STEM Education Outcomes - Amina Mama; George Owusu; Charles Shey Wiysonge (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study assesses the effectiveness of peer tutoring programs in enhancing students' performance in STEM subjects (Science, Technology, Engineering, and Mathematics). A longitudinal analysis of a peer tutoring initiative in a high school setting revealed significant improvements in both the academic performance of tutees and the tutoring skills of peer tutors. The research highlights the mutual benefits of peer tutoring, with tutees gaining better understanding of STEM concepts and tutors reinforcing their own knowledge. The findings suggest that peer tutoring is a valuable pedagogical tool in STEM education.